Culturally responsive public speaking: Elevating high school students' rhetorical competence through South Sumatran local wisdom - Izzah Izzah; Hani Atus Sholikhah; Fikri Fikri; Chrisnatama Tangguh Prasetyo (Community Empowerment, 2026)
Public speaking education in high schools often lacks contextual relevance, missing opportunities to connect communication skills with cultural heritage. This community service initiative addresses this gap by enhancing the public speaking competence of SMAN students in South Sumatra, embedding local wisdom as a rich rhetorical foundation to foster regional cultural preservation. The program deployed an educational-participatory framework that integrated interactive training, project-based learning, and hybrid mentoring (blended learning). The intervention yielded a substantial transformation in students' oratorical proficiency, with mean performance scores shifting from a baseline of 2.07 on the pretest to 3.59 on the posttest. The most pronounced advancements were observed in students' ability to weave local pantun (traditional poetry) and proverbs into their speeches, maintain cultural relevance, practice linguistic politeness, and use authentic South Sumatran honorifics. Beyond sharpening technical delivery, the program significantly bolstered students' confidence, deepened their cultural identity, and enabled them to leverage digital media for culturally grounded communication. Ultimately, this culturally responsive public speaking model serves as a highly effective, scalable, and sustainable tool for contemporary communication literacy.